PECULIARITIES OF GROUNDWATER CHEMICAL COMPOSITION IN EOCENE AND ALBIAN-CENOMANIAN TERRIGENOUS SEDIMENTS IN THE DNIPRO BASIN - LYUTA, Natalia; SANINA, Iryna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The Dniprovsko-Donetskyi Artesian Basin is the largest hydrogeological region of the first order in Ukraine in both area and resources. The main forecasted resources within its boundaries are confined to the Eocene aquifer and the Alb-Cenomanian aquifer complex. These aquifer and complex are the principal ones - they are the basis for centralized water supply of a number of large settlements, so studying their chemical composition is of exceptional importance. The parts of the mentioned aquifer and complex that contain drinking water are identified as groundwater bodies (GWBs) – groundwater monitoring objects for which environmental objectives and risks of failure to achieve these objectives should be determined. At the same time, the natural water quality composition of these groundwater bodies groups is characterized by significant spatial heterogeneity, which should be taken into account when determining trends in its changes and specifying environmental objectives. The aim of the study was to establish the peculiarities of the spatial distribution of water with different chemical composition. The object of the study was aquifers in Eocene and Alb-Cenomanian sediments within the Dniprovsko-Donetsky artesian basin (Dnipro River Basin), and the subject was the chemical composition of water in these aquifers. Methods. To achieve these purposes, data on the chemical composition of the aquifer in the Eocene sediments and the aquifer complex in the Alb-Cenomanian sediments were collected, summarized and analyzed from published and fund sources. The information was processed using geographic information systems, and a database was created to generate specialized maps and perform joint data analysis. Results. In the article the mineralization and macrocomponent composition of groundwater in the terrigenous sediments of the Eocene and Albian-Cenomanian of the Dnipro basin are investigated and the peculiarities of their spatial distribution are established. Particular attention is paid to the areas where the exploitation reserves of both groundwater aquifers are explored. The qualitative, including microcomponent, composition of groundwater in terrigenous sediments of the Eocene and Albian-Cenomanian in Chernigiv City was characterized in detail. Peculiarities of formation of the chemical composition of groundwater in terrigenous sediments of the Eocene and Albian-Cenomanian were established.  Сonclusions. It has been established that despite the fact that both GWBs are located in the zone of active water exchange, the content of macro- and microcomponents in them is quite different. In particular, in the water in the Alb-Cenomanian sediments, the macrocomponent composition of water is more homogeneous, and the content of macro- and microcomponents is characterized by a smaller range of variation. The identified peculiarities of the natural quality composition of the studied GWBs should be taken into account in the process of groundwater monitoring, in particular, when specifying environmental objectives and determining the frequency of groundwater quality state observations.
Keywords: Dniprovsko-Donetsky artesian basin; groundwater bodies in Eocene sediments; groundwater bodies in Albian-Cenomanian sediments; groundwater quality state; mineralization; hydrochemical zoning